2012
DOI: 10.1371/journal.pone.0044668
|View full text |Cite
|
Sign up to set email alerts
|

Early Vascular Alterations in SLE and RA Patients—A Step towards Understanding the Associated Cardiovascular Risk

Abstract: Accelerated atherosclerosis represents a major problem in both systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA) patients, and endothelial damage is a key feature of atherogenesis. We aimed to assess early endothelial changes in SLE and RA female patients (127 SLE and 107 RA) without previous CV events. Biomarkers of endothelial cell activation (intercellular adhesion molecule-1 (sICAM-1), vascular cell adhesion molecule-1 (sVCAM-1), thrombomodulin (TM), and tissue factor (TF)) were measured and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
42
2
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(50 citation statements)
references
References 47 publications
(46 reference statements)
2
42
2
4
Order By: Relevance
“…In the present work, the mean levels of serum Ang-2 serum levels were elevated in all SLE patients (with and without nephritis), compared with healthy controls which agreed with those described previously [9,21], they found that Ang-2 was significantly elevated in SLE patients. Moreover the current work showed that, serum Ang-2 levels were significantly higher in patients with LN than in those without nephritis.…”
Section: Discussionsupporting
confidence: 93%
“…In the present work, the mean levels of serum Ang-2 serum levels were elevated in all SLE patients (with and without nephritis), compared with healthy controls which agreed with those described previously [9,21], they found that Ang-2 was significantly elevated in SLE patients. Moreover the current work showed that, serum Ang-2 levels were significantly higher in patients with LN than in those without nephritis.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, it has been shown that early vascular alterations and endothelial cell activation biomarkers are more pronounced in patients with SLE, which is in line with the high cardiovascular risks observed in such patients 33) . An elevated level of whole blood TF procoagulant correlates with the increased formation of β2GPI/anti-β2GPI complexes in monocytes.…”
Section: Discussionmentioning
confidence: 53%
“…Before our patient showed calciphylaxis symptoms, she was diagnosed with SLE and APS. Autoimmune diseases lead to endothelial damage [7]. SLE patients, especially those with APS, tend to have arterial calcification [8].…”
Section: Discussionmentioning
confidence: 99%